Growth and Yield of Taro (Colocasia esculenta (L) Schott.) as Affected by Planting Distance - Richard Boampong; Samuel Kwasi Boateng; Richard Adu Amoah; Bright Adu Gyamfi; Lawrence Misa Aboagye; Eric Osafo Ansah (International Journal of Agronomy)
Taro, Colocasia esculenta (L) Schott., is a staple food for many people in Africa. Despite the numerous importance of the crop, it still remains an underutilized crop in Ghana with little information on many aspects of the crop, especially agronomic practices. This experiment was conducted to identify the effect of planting distance on growth and yield of two promising taro accessions. The experiment was laid out using the split-plot design arranged in Randomized Complete Block Design (RCBD) with three replications in which accessions (BL/SM/80 and BL/SM/16) were used as main plots and three planting distances (1 m × 1 m, 1 m × 0.75 m, and 1 m × 0.5 m) as subplots. Data were recorded on the 4th, 8th, 12th, 16th, 20th, 24th, and 28th week after planting (WAP) for growth parameters while yield data were taken at harvest. The results indicated that plant height (63.4 cm), petiole length (44.0 cm), number of leaves (4.7), leaf length (31.7 cm), and width (20.5 cm) were significantly (P≤0.05) higher in closely spaced plants than widely spaced plants at 4 WAP and 8 WAP for petiole length (70.3 cm) and in the 28th WAP where there was an accession effect on leaf length and number of suckers/plant. The highest corm yield/plant (0.63 kg) and total corm yield/ha (11.7 t/ha) in both accessions were achieved by the medium plant spacing (1 m × 0.75 m) and lower plant spacing (1 m × 0.5 m), respectively. Accession BS/SM/80 recorded the highest total yield/ha of 13.0 t/ha for 1 m × 0.5 m plant spacing. The higher number of suckers (8.1) was recorded by higher spaced plants. From the study, it was seen that growth parameters correlated significantly and positively with yield. It is therefore recommended that farmers in the area and those in similar production areas use a spacing of 1 m × 0.5 m for optimum growth and yield.